AI in AML: innovative approaches and potential to improve financial literacy of the population - Kusainova, L.K.; Albekova, M.G.; Dulatbekov, N.O. (Karagandy University of the name of academician E.A. Buketov, 2025)
The purpose of this study is to analyze the use of artificial intelligence (AI) for anti-money laundering (AML) and explore the potential of AI to improve the financial literacy of citizens in order to prevent fraud and participation in money laundering. With the development of modern technology, the ways in which crimes are committed have significantly changed, become more complex and transformed, especially the large-scale cyber-attacks that occur on a daily basis. Therefore, in the current realities, it is necessary to utilize effective technological solutions that can respond quickly to new threats. One such way is the application of artificial intelligence (AI) technologies, which is widespread across various industries, and AML is no exception. The study found that the advantage of using artificial intelligence in AML compliance is its functionality to allow for real-time monitoring and analysis. This makes it possible to detect potential threats or possible illegal activities in which citizens are involved, consciously and unconsciously, and conduct thorough investigations to protect citizens and the state. The main result, which the authors have reached, consists in practical proposals, based on foreign experience, to introduce AI into the AML systems of the Republic of Kazakhstan to detect, report and suppress suspicious money laundering operations.
AML саласындағы ЖИ: инновациялық тәсілдер және халықтың қаржылық сауаттылығын арттыру әлеуеті
ИИ в сфере AML: инновационные подходы и потенциал повышения финансовой грамотности населения
Keywords: money laundering; artificial intelligence; digital technology; anti-fraud; citizen financial security; scams